Trends in point-of-care ultrasound protocols in the emergency department and intensive care unit: a review - Xinhui Fan; Yuan Bian; Guoying Wang; Weikang Liu; Luyao Gao; Yuhui Pan; Shengchuan Cao; Qiuhuan Yuan; Shujian Wei; Feng Xu; Yuguo Chen (Emergency and Critical Care Medicine)
Abstract. Together with the development of the focused assessment with sonography for trauma protocol for ultrasound in trauma patients, point-of-care ultrasound is widely used in the field of emergency and critical care medicine. Researchers have established several classic operating protocols for different diseases, such as acute respiratory failure, shock, and cardiac arrest, in the emergency department and intensive care unit. With further development in the portability and popularity of ultrasonic equipment, it is expected to be used as a new type of technology for physical examination, including inspection, palpation, percussion, auscultation, and insonation, which will improve the clinical medicine practice in the future.